Analysis of measurements to calibrate pulse energy for main ablation experiment - van Oosten, Dries; Vreugdenhil, Marnix (Utrecht University, 2022)
This folder contains the analysis used to calibrate the pulse energy (as measured using the auxiliary camera in the setup) with respect to a TD10XP thermopile sensor mounted in the sample plane under the ablation objective. The relevant data were taken on 20210916. These were taken to calibrate measurements done on 20210729.
Keywords: Natural Sciences - Physical sciences (1.3); yoda